Synthesis of glycoimmunogen Tn-Thr-PS A1 via hydrazone bond and stability optimization of PS A1 monosaccharide mimics under vaccine development conditions. Issue 2 (23rd March 2020) - Hossain, F.; Nishat, S.; Ghosh, S.; Boga, S.; Hymel, G. T.; Andreana, P. R.
Abstract: Previously, our group constructed several immunogens utilizing oxime linkage to conjugate a T-cell stimulatory zwitterionic polysaccharide PS A1 and tumor associated carbohydrate antigens (TACAs) in acetate buffer. Here, a semi-synthetic immunogen was synthesized using hydrazone conjugation between PS A1 and a glycopeptide hydrazide (α-D-GalNAc-L-Thr-NH-NH2 ) with an excellent loading in PBS buffer. To get robust immune response, the retention of zwitterionic character of PS A1 under vaccine construction conditions is essential. In this regard, the stability of embedded pyruvate acetal moiety in tetrasaccharide repeating unit of PS A1 can validate the retention of the dual charges. Therefore, rather than utilizing this highly immunogenic PS A1 fully, stability studies were performed with synthetic 1-thiophenyl-4, 6- O -pyruvate acetal-D-galacto pyranose in varying acetate buffer pHs and time intervals. Furthermore, 1-propyl-D-galacto furanose was synthesized to mimick the D-Gal f of PS A1 to examine regioselective hydrazone and oxime formation with α-D-GalNAc-L-Thr-NH-NH2 and α-D-GalNAc-ONH2 moieties respectively. Graphical Abstract: